Elderly in the Perspective of Minangkabau Nagari Aie Dingin of Solok Regency of West Sumatera Province - Agus, Fitri; Elsera, Marisa; Wahyuni, Sri (TEMALI : Jurnal Pembangunan Sosial, 2022)
Minangkabau people are very well known for their customs which are interesting to know and study. The existence of the Nagari government illustrates how a customary-based governance system governs the Minangkabau community's life. The role of ulayat land explains assets or properties and their benefits for clan members' security. Women's existence and function explain the degree of their role in family and community life. The function and existence of sponsorship for the elderly explains the model and form of sponsorship for the elderly. The purpose of this research is to know the life of the elderly if in the study of Minangkabau Culture in Nagari Aie Dingin of Solok Regency of West Sumatra Province. This study used qualitative methods and descriptive types, data collection was carried out using observation methods, interviews using interview guides and documentation. Data analysis in this study uses the Miles and Huberman model: data reduction, data presentation, conclusion and verification. The findings in this study indicate that with the high level of population aged 60 years and over, many elderly people are still actively working and the communal system is less active. Older women are prioritized over older men in Minangkabau.